2009
DOI: 10.1136/vr.164.24.751
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation of six dogs anaesthetised with isoflurane or sevoflurane delivered by a Komesaroff anaesthetic machine

Abstract: After intravenous induction, six beagles were connected to a Komesaroff machine provided with a single in-circuit vaporiser and ventilated mechanically at either nine or 14 breaths/minute while anaesthetised with either isoflurane or sevoflurane. The vaporiser was initially set at position 4/4 (fully open) and the anaesthetic concentrations were measured after one and five minutes; the vaporiser was then set at the lowest setting able to maintain anaesthesia. Cardiorespiratory variables were measured throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…13 Several animal studies have shown that volatiles anesthesia has a protective effect on myocardial infarction. [14][15][16][17] Human studies also indicate that these drugs have the potential to provide adequate anesthetic depth. Moreover, these drugs have protective effects on myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several animal studies have shown that volatiles anesthesia has a protective effect on myocardial infarction. [14][15][16][17] Human studies also indicate that these drugs have the potential to provide adequate anesthetic depth. Moreover, these drugs have protective effects on myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%